The role of fault reactivation in the geomorphological evolution of coastal landforms on passive continental margins: Evidence from a tectonic estuary in southern Brazil - Gimenez, Viviane Barbosa [UNESP]; Salamuni, Eduardo [UNESP]; dos Santos, Jéssica Miranda [UNESP]; Peyerl, William Rudolf Lopes [UNESP]; Farias, Taily Ferreira Santos [UNESP]; Sanches, Emerson [UNESP] (Elsevier, 2022)
Coastal areas are unique, fast-changing environments shaped by the action of a wide range of climatic, anthropogenic and geological factors. Tectonic processes (e.g., subsidence, uplift, faulting and tilting) are major controls of landscape evolution and may be responsible for significant changes in river catchments, sea level and erosion rates on coastal zones. In continental passive margins, however, strong tectonic influence is typically attributed to early post-rift evolutionary stages, while changes in climate and/or sediment flux become increasingly dominant in the latest phases. However, there are key exceptions to this rule. We provide new results on an estuarine system formed due to reactivation of major structures crossing the southern edge of Serra do Mar escarpment, where Precambrian terrains, Cretaceous volcanic rocks and Neogene coastal deposits coexist. Morphostructural analysis revealed strong morphometric anomalies near Proterozoic fault zones marked by local subsidence and reactivation of oblique and normal faults, responsible for relevant changes in coastal landscape and tilting of the coastal plain towards the Atlantic Ocean. Despite major Late Holocene progradation along the southern Brazilian coast, local subsidence led to development and preservation of Babitonga Bay, an atypical tectonic estuary formed in the latest stages of passive margin evolution. Our findings imply that the common assumption of recent tectonic stability for intraplate passive margins is false and may lead to misinterpretation of similar coastal systems around the world.
Keywords: Coastal landforms; Fault reactivation; Morphotectonics; Tectonic estuary